2022
DOI: 10.1186/s12873-022-00650-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors associated with intravenous fluid administration in patients with sepsis presenting to the emergency department: a retrospective cohort study

Abstract: Background Appropriate and timely administration of intravenous fluids to patients with sepsis-induced hypotension is one of the mainstays of sepsis management in the emergency department (ED), however, fluid resuscitation remains an ongoing challenge in ED. Our study has been undertaken with two specific aims: firstly, for patients with sepsis, to identify factors associated with receiving intravenous fluids while in the ED; and, secondly to identify determinants associated with the actual tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Intravenous (IV) fluid administration is a fundamental part of the management of patients with acute infectious disease. Previously published retrospective studies showed that most patients admitted with sepsis and septic shock received early and aggressive treatment with IV fluids [1,2]. However, multiple studies, including high-quality randomized controlled studies, that examined a protocol-based approach to early and goal-directed IV fluid treatment in patients with sepsis and septic shock have demonstrated mixed results [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous (IV) fluid administration is a fundamental part of the management of patients with acute infectious disease. Previously published retrospective studies showed that most patients admitted with sepsis and septic shock received early and aggressive treatment with IV fluids [1,2]. However, multiple studies, including high-quality randomized controlled studies, that examined a protocol-based approach to early and goal-directed IV fluid treatment in patients with sepsis and septic shock have demonstrated mixed results [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%